Efeitos do peso adicional nos chutes espontâneos de lactentes nos primeiros dois meses de vida - Landgraf, Jocelene de Fátima (2006)
This study aimed to characterize the spontaneous kicking patterns in 1-and-2-monthold infants, as well as verify whether the extra weight of 1/10 and 1/3 of the leg mass can modify such patterns. Eight infants were longitudinally recorded in supine at 1 and 2 months of age. The experiment lasted six minutes and twenty seconds, and was subdivided into five conditions: (1) training: the examiner put the infants right foot, then their left foot, and finally their feet simultaneously on a board three times running in order to make them raise the board and start the mobile. (2) Baseline: while kicking, the infants used their feet to raise the board and start the mobile; (3) Extra Weight 1: the same as the baseline condition, but with the weight of 1/10 of the leg mass on the ankle; (4) Extra Weight 2: The same as the baseline condition, but with the weight of 1/3 of the leg mass on the ankle; (5) Post-weight: the same as the baseline condition. Frequency of kicking, frequency of feet contact with the board when starting the mobile, uni and bipodal movements, and lateralization were verified by analyzing the images. In order to analyze intralimb coordination pattern, kicking duration, mean velocity, and straightness index, the kinematic analysis was applied by using the Dvideow System 6.3. The Chi-Square test indicated a significant increase in the frequency of kicking at 2 months and in the conditions of extra weight 1 and postweight. The frequency of feet-contact with the board decreased in the condition of extra weight 2, and increased at 2 months. Unilateral kicking was predominant in all the conditions and ages, and infants showed no preference for either leg. The Kruskal- Wallis test indicated no significant differences in the intralimb coordination pattern among the conditions or ages. However, hip-knee correlation was shown to be high, indicating that these articulations are in-phase when kicking. The ANOVA for repeated measures showed no significant differences in kicking duration, mean velocity, and straightness index. In summary, kinematic variables were not altered with extra weight or increased age. Therefore, it is possible to suggest that the infants changed the frequency of kicking at 1 and 2 months of age due probably to intrinsic factors (e.g. increased mass and muscle strength, infants behavioral state, maturation of the Central Nervous System) and extrinsic factors (e.g. interest in interacting with the environment and performing the proposed tasks). Furthermore, the infants spontaneous kicking was influenced by the stimulation of the proprioceptive system when bearing the extra weight of 1/10 of their leg mass.